Fast Distance Fields for Fluid Dynamics Mesh Generation on Graphics Hardware (Communications in Computational Physics, 2019)
We present a CUDA accelerated implementation of the Characteristic/Scan Conversion algorithm to generate narrow band signed distance fields in logicallyCartesian grids. We outline an approach of task and data management on GPUs basedon an input of a closed triangulated surface with the aim of reducing pre-processingand mesh-generation times. The work demonstrates a fast signed distance field generation of triangulated surfaces with tens of thousands to several million features inhigh resolution domains. We present improvements to the robustness of the originalalgorithm and an overview of handling geometric data.